P94 Patient Agenda Setting And Clinic Efficiency In Outpatients: An Individual Randomised Controlled Trial. (10th November 2014) - Everden, A; Early, F; Homan, K; Fuld, J
Abstract : Introduction: Most patients have issues to raise in a consultation but may not actually raise them, adversely affecting the consultation outcome. Evidence suggests that methods to help patients consider their information needs before a consultation can increase satisfaction without increasing consultation length but there is a need to assess a wider range of outcome measures and to measure consultation length accurately. We studied the impact of a paper agenda form to prompt question asking in a respiratory outpatient clinic. The primary objective was to identify whether this increased agreement that "My doctor discussed the issues that were important to me". Secondary endpoints included consultation length and post-consultation confidence to self-manage (0–10 scale). Method: Patients were randomised to receive the agenda form or usual care by blocked randomization (block size 6), stratified by consultant. Patients receiving the form had a written brief inviting them to complete it in the waiting room. PROMs were collected post-consultation. Consultations were timed by an observer outside the room. As planned in the protocol, categorical data were analysed using Fisher's exact test and continuous data were analysed using a t-test. Exploratory analyses to assess the effects of a number of factors used mixed model ANOVA. Results: Groups were well matched at baseline for age, gender and respiratory diagnosis. There was no significant effect of agenda form use on the primary or secondary endpoints (Table 1). Exploratory analyses identified that in new patients (but not in follow-up patients) the form was associated with shorter consultation length (LS mean=15.2 mins) than usual care (LS mean=21.3 mins) (p = 0.017) and with lower confidence to self-manage (LS mean=6.6) than usual care (LS mean=9.2) (p = 0.001). Conclusion: There was no overall benefit from the form and a risk of detrimental impact on patient experience for some patients. This resonates with reports from other more complex self-management interventions that have found unexpected detrimental effects in some patients. There is a need for greater understanding of what works for whom with regard to self-management support. It cannot be assumed that the impact will be universally beneficial at best or neutral at worst. Reference: Trial reference: REC reference: 13/WA/0171